Improved Method for Use of Hand Gesture Recognition with CNN Algorithm by Using Opencv Data Sets - G. Tarun Datta (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The capacity of computers to detect and comprehend human hand motions as input is known as hand gesture recognition. Virtual reality, human-computer interfaces, and sign language interpretation are just a few of the many fields that make use of this technology. Hand gesture recognition uses several approaches. When it comes to capturing and analyzing motions, vision-based approaches rely on cameras or comparable visual sensors, whereas touch-based techniques use sensors or sensitive surfaces for the same purpose. Hand gestures may have vastly different meanings depending on the culture and context. Some cultures may find hand gestures to be an effective means of communication, while others may find them to be very disrespectful. Depending on the situation in which they are used, the meaning of some gestures may also change. In certain cultures, the gesture "thumbs up" is seen as a favorable indication, whereas in others, it is considered insulting. It is crucial to recognize the cultural context in which gestures are performed, and to take into account that various people will perceive them differently. Researchers have created trustworthy characteristics and classifiers for accurate identification, as well as strategies to deal with these differences, such as background exclusion and hand segmentation. In conclusion, the healthcare, educational, and entertainment industries might all benefit from hand gesture recognition’s capacity to increase the efficiency and usefulness of computer interactions.